Nutrition for optimal performance - Clark, Kristine; American College for Sports Medicine ([Indianapolis, In.] : Monterey Bay Video Production Co., 2004)
Discusses the body's need for macronutrients and micronutrients and reviews what foods to choose to maximize performance. The video details the most appropriate sources of training fuel foreach of the three nutrients that provide energy
Title from title screen
Keywords: Nutrition; Exercise; Physical fitness